THE CORRELATION BETWEEN VOCABULARY MASTERY AND READING COMPREHENSION IN DESCRIPTIVE TEXT OF STUDENTS AT SMA NEGERI 3 TONDANO - Ni Nengah Walansih; Ignatius J. Tuerah; Paula Hampp (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2023)
The purpose of this research was to know the correlation between vocabulary mastery and reading comprehension in descriptive text of students at SMA Negeri 3 Tondano. The test method was used in this quantitative research, which was a type of correlation research. Students in class XI IPA 1 were the focus of this research consisted of 26 students. The data collection technique used multiple-choice objective tests with a total of 50 questions, each for a vocabulary mastery test of 25 numbers and a student's reading comprehension test of 25 numbers. From the calculation of hypothesis testing through the use of the Pearson product moment correlation test seen from the significance value of 0.001 < 0.005 then it was correlated and the Pearson correlation value is 0.0679 based on the norm, the degree of correlation lies in the Pearson correlation value of 0.60 to 0.80, meaning the correlation between vocabulary mastery and students' reading comprehension was included in the category of strong correlation. Because the Pearson correlation value is 0.679, it can be concluded that the students' vocabulary mastery and reading comprehension of the students' descriptive text at SMA N 3 Tondano have a positive correlation.